Gene-based therapy of malignant melanoma - Schadendorf, Dirk (Seminars in oncology, 2005)
Melanoma continues to present a major therapeutic challenge to oncologists, oncologic surgeons, and dermatologists. Recent advances in molecular genetics and improvement in our understanding of immune responses to tumors have generated an interest in using gene-based treatment strategies to fight melanoma. Several basic strategies have emerged: (1) strengthening of the immune response against tumors by genetic modification of some target cell populations of the host using immunostimulatory genes such as cytokines and by genetic immunization with the genes coding for melanoma-associated antigens recognized by cytotoxic T cells; (2) interference with signaling cascades; and (3) suicide gene strategies. This article reviews these novel strategies and summarizes the most recent data generated by European groups either in experimental studies or in clinical trials. Semin Oncol 29:503-512. Copyright 2002, Elsevier Science (USA). All rights reserved.
Elektronische Reproduktion der Druckausgabe
Gesehen am 17.11.2020